"Survival is insufficient": The Postapocalyptic Imagination of Emily St. John Mandel’s Station Eleven - Maximilian Feldner (Anglica. An International Journal of English Studies)
Postapocalyptic narratives proliferate in contemporary fiction and cinema. A convincing and successful representative of the genre, Emily St. John Mandel’s Station Eleven (2014) can nevertheless be distinguished from other postapocalyptic texts, such as Cormac McCarthy’s The Road (2006), Margaret Atwood’s Maddaddam trilogy, and the television series The Walking Dead (2010–). The novel does not focus on survival, struggle, and conflict but rather examines the possibility and necessity of cultural expression in a postapocalyptic setting, demonstrating the importance and value of art and memory even in strained circumstances. As a result, it presents an unusually optimistic and hopeful vision of an otherwise bleak future.